Implementation of Karawang City Government Communication to the Community Regarding the Tangkar Application - Nariswari, Qinthara Malta; Yudha, Teza; Ramdani, Rachmat (Journal of Government Science Studies, 2026)
This study aims to analyze the implementation of communication by the Karawang City Government in utilizing the TANGKAR application as an e-government–based public complaint system. The research employs a qualitative approach using in-depth interviews, observation, and documentation involving ten informants, consisting of officials from the Department of Communication and Informatics (Diskominfo), sub-district and village administrators, and members of the public who use the application. The findings indicate that government communication in the socialization and management of the TANGKAR application has been conducted through various digital channels; however, it still faces challenges related to message consistency, public digital literacy, and inter-agency responsiveness. The novelty of this study lies in positioning strategic communication as the primary variable in analyzing the effectiveness of a digital public complaint system, rather than focusing solely on the technical or policy aspects of e-government implementation. Therefore, this study provides a conceptual contribution by expanding the discourse on local-level e-government through a strategic communication perspective, while also offering empirical recommendations to strengthen public participation and improve the quality of digital-based public services.